Relevance of educational technology competence as human resources in the apprentice industry - Muhammad Nur Iman Hadiyana Setia; Lies Diana Dwi Irawati; Yurike Ahsani Putri (Curricula: Journal of Curriculum Development, 2023)
The profession of an Educational Technologist in Indonesia is increasingly diverse; by looking at the fundamental conceptions of Educational Technology and current employment developments, the urgency of this profession is starting to be recognized by the government. This is evidenced by the ratification of the Peraturan Menteri Pendayagunaan Aparatur Negara Nomor: PER/2/M.PAN/2009 tentang Jabatan Fungsional Pengembang Teknologi Pembelajaran dan Angka Kreditnya. To deal with this, Educational Technology scholarship must be able to anticipate it in a more systematic and systemic provision so that it can overshadow the professions in the field of Educational Technology. This study aims to determine the implementation and relevance of Educational Technology competencies by further examining the Human Resource profession in the Apprentice Industry Sector based on facts that occur in the world of work. This study uses a qualitative method with a descriptive approach. The data source was obtained from interviews with three respondents: three educational technology study program students doing internships in related professions. The research results found that Educational Technology's role in human resources is related to the operational function of development. Educational Technology is related to designing, preparing, implementing, and evaluating training programs to develop employee skills and performance.